Integration between management and accounting and its role in enhancing the effectiveness of planning and control - Abdullah, Abadelrhem Abdullah Abubakir; Mohamed, Rayad Ibrahim Saleh (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to explore the impact of integrating management and accounting on improving planning and control efficiency, ensuring sustainability, and enhancing organizational performance. The study employs a mixed-method approach, including descriptive analysis to examine key factors influencing integration, a quantitative approach for data collection and analysis, and a comparative method to evaluate prior research findings. The results indicate that integration between management and accounting enhances strategic planning efficiency by 70% in some global companies. It also improves interdepartmental coordination, leading to a 30% increase in operational efficiency and a 25% reduction in financial waste. Furthermore, firms with integrated management and accounting systems achieve higher growth and sustainability rates compared to those lacking such integration. The study recommends strengthening communication channels between departments, adopting integrated information systems to support decision-making, and investing in employee training to ensure effective integration between management and accounting.